2020
DOI: 10.2298/tsci190602459s
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analysis of greenhouse drying of ivy gourd and turkey berry

Abstract: Original scientific paper https://doi.org/10.2298/TSCI190602459SThis study deals with the performance evaluation of a simple low-cost greenhouse dryer using energy and exergy analysis. Drying experiments were conducted under the open Sun and in greenhouse dryer with two different cover sheets of ultra violet polyethylene and drip lock under passive mode and active mode for two vegetables with medicinal values: ivy gourd (coccinia grandis) and turkey berry (solanum torvum). Thermal efficiency, exergy efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…It was observed that the convective heat transfer coefficients of dried three products, namely gurjo, Turmeric and Ginger, were varied from 1.57-3.85, 2.32-3.42 and 1.62-3.34W/m 2 °C. Subramani et al (2020) fabricated the natural and forced convection greenhouse solar dryer for drying two different samples, namely ivy gourd and turkey berry. It was determined that the thermal efficiency of the greenhouse dryer found to be 30.6%.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the convective heat transfer coefficients of dried three products, namely gurjo, Turmeric and Ginger, were varied from 1.57-3.85, 2.32-3.42 and 1.62-3.34W/m 2 °C. Subramani et al (2020) fabricated the natural and forced convection greenhouse solar dryer for drying two different samples, namely ivy gourd and turkey berry. It was determined that the thermal efficiency of the greenhouse dryer found to be 30.6%.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were conducted for drying turkey berry under open sun drying, UV polyethylene as glazing material, drip lock sheet as glazing matrial under passive and active mode [21] .The following conclusions were drawn from the results obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The average exergy efficiencies are 2.4 % and 2.6 % for the 10 kg and 5 kg loads respectively, and are lower than the energy efficiencies. Tiwari, Des, Chen and Barnwel (2009) in the greenhouse drying of fish, and Subramani, Dana, Natesan, and Leo (2020) in the greenhouse drying of ivy gourd and turkey berry, also found that the exergy efficiency was lower than the energy efficiency and attributed this to some of the input exergy being destroyed due to irreversibility.…”
Section: Resultsmentioning
confidence: 99%